PENGGUNAAN MODEL PIMCA BERBASIS MULTI REPRESENTASI PADA PEMBELAJARAN HUKUM I TERMODINAMIKA - Putri Winda Sirait; Jeane Cornelda Rende; Satyano Mongan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
This research focused on physics material, the first law of thermodynamics with PIMCA model based on multi-representation. PIMCA (Presentation, Idea Mapping, Conceptualization, Assessment Formative). The purpose of this research is to know the result of students’ learning after taught used PIMCA learning model based on multi-representation on the first law of thermodynamics using SPSS. The method used is One Pre-test-Post-test Design. This research was conducted at SMA N 1 Remboken with 30 respondents. The procedure was start with pre-test then continuing with learning physics by following the four steps of PIMCA model and then ended with post-test. The data that found from the research are: the pre-test’s average is 33,66 and post-test average is 71,48. Generally the students gave positive responses on PIMCA learning model.This research, it can be concluded that there is an enhancement of students’ learning result in learning the first law of thermodynamics. This research makes the students become more active in getting the knowledge and makes them think creatively. The result of the research showed that PIMCA learning model based on multi-representation is very effective to use in learning the first law of thermodynamics.